2016
DOI: 10.1016/j.celrep.2016.09.066
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Grammar Defines Activating and Repressing cis-Regulatory Elements in Photoreceptors

Abstract: Summary Transcription factors often activate and repress different target genes in the same cell. How activation and repression are encoded by different arrangements of transcription factor binding sites in cis-regulatory elements is poorly understood. We investigated how sites for the transcription factor CRX encode both activation and repression in photoreceptors, by assaying thousands of genomic and synthetic cis-regulatory elements in wild-type and Crx−/− retinas. We found that sequences with high affinity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
144
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(168 citation statements)
references
References 52 publications
(93 reference statements)
24
144
0
Order By: Relevance
“…Our results indicate that, with the notable exception of pSTATs, the mere presence or absence of binding motifs for specific TFs cannot predict individual cis-regulatory responses to TPO and raise the possibility that orientation and spacing of TF motifs might play a role in determining these responses. Consistent with this concept, a recent work demonstrated that a different motif grammar based on the same building blocks defines activating and repressing cis-regulatory elements in rod photoreceptors (White et al 2016).…”
Section: Discussionmentioning
confidence: 70%
“…Our results indicate that, with the notable exception of pSTATs, the mere presence or absence of binding motifs for specific TFs cannot predict individual cis-regulatory responses to TPO and raise the possibility that orientation and spacing of TF motifs might play a role in determining these responses. Consistent with this concept, a recent work demonstrated that a different motif grammar based on the same building blocks defines activating and repressing cis-regulatory elements in rod photoreceptors (White et al 2016).…”
Section: Discussionmentioning
confidence: 70%
“…Indeed, several photoreceptor genes are known to be regulated by NRL/CRX co-occupancy within their regulatory regions (Hao et al, 2012; White et al, 2016). Interestingly, a similar co-regulatory function of NRL/CRX appears to hold true in Group 3 MB.…”
Section: Discussionmentioning
confidence: 99%
“…These TFs act in concert during photoreceptor differentiation and synergize to regulate the expression of photoreceptor genes (Hsiau et al, 2007). Consensus binding sites for NRL and CRX often coincide and are enriched in regulatory elements of photoreceptor genes (Hao et al, 2012; White et al, 2016). Knockout of either TF in mice induces strong defects in photoreceptor differentiation and mutations in humans are linked with retinopathies (Swaroop et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Characterization studies examine thousands of different putative regulatory elements that have a wide variety of sequence features and try to correlate these sequence features with measured activity levels (Grossman et al, 2017;Guo et al, 2017;Safra et al, 2017;Levo et al, 2017;Maricque, Dougherty, and Cohen, 2017;Groff et al, 2016;Ernst et al, 2016;White, Kwasnieski, et al, 2016;Ferreira et al, 2016;Fiore and Cohen, 2016;Farley et al, 2015;Kamps-Hughes et al, 2015;Dickel et al, 2014;Kwasnieski, Fiore, et al, 2014;Mogno, Kwasnieski, and Cohen, 2013;Gisselbrecht et al, 2013;White, Myers, et al, 2013;Smith et al, 2013). Typical statistical analyses use regression to study the impact of multiple features simultaneously.…”
Section: Introductionmentioning
confidence: 99%